(3QaY GdSJhQ hGdCQGFc Yf eNHBJ ChVM GdeSGdcs - (3eMj GdOjf YHO GdbGOQ Hf CHj GdbGSe Hf CMeO GdCfUGQj GdSYOj GdeGdcjs; (3YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg Hf jhSa , GHf gTGe , LeGd GdOjf , CHh eMeO,J (B761 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg Pj GdLdGd hGdEcQGe CeG HYO MeO Gddg Cbhd(B: (3GaJJM cJGHg HMeO Gddg SHMGfg COGA dMb TF eeG jLH Ydjg ef TcQ fYeg s
(3BNQgG (B:s
(3HaJM GdgeRI hcSQ GddGe eYfGg JZjQJ QGFMJg, hGddg CYde bGd eDdagG hgPG BNQ eG JjSQ HYh Gddg LeYg hJSgd Hef Gddg hVYg, hGdMeO ddg s
(3ChVM GdeSGdc GdeTghQ HGdJhVjMs
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3HgG fXGe GdJYbjHIs
(3HgG CKQ WeS s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdfMhs